Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Social Action Budget Brief - Mozambique 2021 - UNICEF and ILO (UNICEF and International Labour Organization (ILO), 2021)
Highlights The 2021 budget for social protection is worth MZN 10.1 billion. This represents a 50 percent nominal increase relative to the 2020 initial allocation (i.e. the first allocation approved by Parliament in 2020) before the onset of the COVID-19 pandemic. However, it represents a 2 percent nominal decrease relative to revised allocation (i.e. the allocation that was revised by Parliament in November 2020 in response to COVID-19), a 4 percent nominal decrease relative to updated allocation (i.e. funds that arrive at the disposal of social protection institutions), and a 26 percent nominal increase relative to the actual expenditure in 2020 (i.e. funds that were spent at the end of budget year) (see Glossary of budget terminology). It is important to highlight that 2020 revised allocation to the sector was exceptionally high as a result of financial support provided by international finance institutions and development partners to implement the sector’s response plan to COVID-19. While part of these funds appeared in the 2020 budget revision, they are de facto being executed in 2021 (i.e. when the actual transfers to beneficiaries of the Direct Social Support Programme - Post Emergency (PASD-PE) are taking place).
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; Social Protection PEA; budget / orçamento; social action / ação social; social protection / proteção social

Mozambique's social protection system: an overview of the Basic Social Subsidy Programme (PSSB), the Direct Social Action Programme (PASD), the Productive Social Action Programme (PASP) and the Social Assistance Services (PAUS) - Arruda, Pedro (International Policy Centre for Inclusive Growth, 2018)
Mozambique has four main social protection responses in place, including a cash transfer programme (the Basic Social Subsidy Programme—PSSB), a food voucher and in-kind transfer programme (Direct Social Action Programme—PASD), a public works programme (Productive Social Action Programme—PASP), and a set of institutional care services for vulnerable adults, elderly people and children without a home (Social Assistance Services—PAUS). We open this brief with an analysis of relevant social protection policies in Mozambique, followed by a description of the institutional set-up of the Mozambican social protection system. The following section discusses the core features of each of the country’s four flagship social policies, assessing the scale of these programmes and how they relate to each other. In the conclusion, we recall previous critiques regarding the excessive amount of categorical criteria mediating eligibility for these Mozambican social protection initiatives. We make the case for expediting the implementation of the recently developed management and information system—e-INAS—in the hope that it will integrate the databases of the flagship social protection initiatives and increase their reach. Most importantly, we question whether the active search for beneficiaries by health workers contributes to the equity of the PASD, and propose impact evaluation studies for the country’s flagship social programmes, which can lead to a rational revamping of the entire social protection system.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Social protection reform in Mozambique and the new basic social security strategy - Falange, Sergio; Pellerano, Luca (International Policy Centre for Inclusive Growth, 2016)
In the framework of efforts to fight extreme poverty and recognising the importance and need to protect the poor and vulnerable population, in 2007 Mozambique approved Law No. 4/2007 which structured social protection into three levels, including basic social security. In 2010 the first National Basic Social Security Strategy (ENSSB I) was approved for the period 2010–2014, including a set of old (e.g. the Basic Social Security Programme—PSSB) and new (e.g. the Productive Social Action Programme—PASP) non-contributory social protection programmes, all implemented by the National Institute for Social Action (INAS) under the policy guidance of the Ministry of Gender, Child and Social Action (MGCAS).
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Mozambique Social Protection Assessment - Review of Social Assistance Programs and Social Protection Expenditures - Marques, José Silvério (World Bank, 2012)
This assessment shows that Mozambique social protection system is developing. While programs to address most of the risks identified exist, there are still major gaps. Poor families with children are not adequately supported, there is no significant youth program, and subsistence farmers and other workers are not properly protected against recurrent shocks. The government spends a considerable amount of its resources on social protection but most are absorbed by untargeted subsidies and pensions that benefit only a few. This assessment suggests that it will be necessary to address three mutually complimentary issues: developing effective mechanisms to maximize the impact of social protection on reducing poverty; rationalizing public expenditures while filling existing program gaps; and strengthening institutional arrangements. In order to address the multiple challenges Mozambique faces to support particularly vulnerable groups and reduce extreme poverty and food insecurity, the report proposes a gradual approach framed in the existing social protection strategy approved by the Government in 2010.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social